Extracellular Vesicles in the Antiphospholipid Syndrome - Chaturvedi, Shruti; Alluri, Ravi; McCrae, Keith R. (Seminars in Thrombosis and Hemostasis, 2018)
Antiphospholipid antibodies (aPL), particularly those directed against β2-glycoprotein I, cause activation of vascular cells (endothelial cells, platelets, monocytes) and release of extracellular vesicles (EVs), which include exosomes and microparticles (MPs). MPs, particularly endothelial MPs, have been most extensively studied in antiphospholipid syndrome (APS). Compared with healthy controls, patients with aPL have significantly higher levels of circulating endothelial and platelet MPs, including MPs expressing immunological and functional tissue factor. Although a consistent relationship of EVs with APS-related thrombosis and obstetric events has not yet been demonstrated, elevated levels of MPs occurring remote from thrombotic events suggest a chronic state of vascular activation in APS. In addition to being a marker of cellular activation, EVs express bioactive lipids, proteins, and nucleic acids, particularly microribonucleic acid (microRNA). EVs may potentially play a pathogenic role in APS by stimulating thrombosis through tissue factor-dependent and independent mechanisms and by promoting vascular activation. Further research is needed to understand these mechanisms and to determine whether EVs may be a useful biomarker to identify patients with aPL at highest risk of clinical events.
Keywords: antiphospholipid syndrome; antiphospholipid antibodies; microparticles; thrombosis; endothelial cells; platelets